Ocean-based negative emissions technologies: a governance framework review - Lina Röschel; Barbara Neumann (Frontiers in Marine Science, 2023)
The model pathways of the Intergovernmental Panel for Climate Change (IPCC) for the timely achievement of global climate targets, especially the target of limiting global warming to 1.5°C compared to pre-industrial levels, suggest the need for safeguarding and enhancing the global carbon sink. Experts argue that the deployment of so-called negative emissions technologies for large-scale carbon dioxide removal holds potential for keeping the temperature in line with limits set by the Paris Agreement. Ocean-based negative emissions technologies (ONETs) intend to enhance carbon sequestration and storage in the ocean, e.g., by changing the ocean’s physical or biogeochemical properties. But in addition to these intended effects, ONETs may also cause unintentional impacts on the ocean’s condition and on related coastal and marine ecosystem services that are relevant for the attainment of a range of global policy goals. This article links potential direct and indirect, intentional and unintentional impacts of eight ONETs on the marine environment to the regulations and policy goals of international environmental agreements of the current global ocean governance regime. The results thereof outline a direct, implicit and indirect governance framework of ONETs. Hereby, a broader perspective of the concept of (global) ocean governance is adopted to outline a wider network that goes beyond the explicit regulation of ONETs within the realm of ocean governance. This first-order assessment derives gaps and challenges in the existing governance framework, as well as needs and opportunities for comprehensive governance of the technologies. It is determined that while the inclusion of ONETs in the global climate strategy may be deemed necessary for reaching net zero emission targets in the future, a range of potential trade-offs with other policy goals may need to be considered or dealt with when deploying ONETS for climate mitigation. Further, foresight-oriented and adaptive governance mechanisms appear imperative to bridge gaps resulting from extensive uncertainties and unknowns linked to ONET deployment in a changing ocean and. The identified ONET governance framework reiterates current challenges in ocean governance, for instance related to fragmentation, but also represents an opportunity for a synergistic and integrated approach to future governance.

Thaliacean community responses to distinct thermohaline and circulation patterns in the Western Tropical South Atlantic Ocean - Everton Giachini Tosetto; Barbara Barkokébas Silva; Xiomara Franchesca García Díaz; Sigrid Neumann-Leitão; Arnaud Bertrand (Hydrobiologia, 2022)

Iron Age plant subsistence in the Inner Congo Basin (DR Congo) - Katharina Neumann; Barbara Eichhorn; Hans-Peter Wotzka (Vegetation History and Archaeobotany, 2022)
Around 400 bc , pottery- and iron-producing populations immigrated into the Inner Congo Basin (ICB) and subsequently spread upstream some major tributaries of the Congo River. Until recently, their subsistence was almost completely unknown. We present an archaeobotanical study of three sites in the ICB covering parts of the Early Iron Age (ca. 400 bc - ad 650) and of the Late Iron Age (LIA) as well as subrecent times (ca. ad 1300–2000). We studied 82 flotated samples of botanical macroremains, and 68 soil phytolith samples, recovered from the terra firme sites Iyonda and Mbandaka, and the floodplain fishing camp site of Bolondo. The EIA assemblage from Iyonda yielded domesticated Cenchrus americanus (pearl millet), Vigna unguiculata (cowpea), Canarium schweinfurthii , Elaeis guineensis (oil palm), several wild plants, and parenchyma fragments tentatively attributed to Dioscorea sp. (yams). The exploitation of these plants originated in the savannas and forest-savanna ecotones of West Africa. The presence of C. americanus in LIA contexts at Bolondo and Mbandaka, dated to ca. ad 1350–1550, indicates that its cultivation is not dependent on a seasonal climate with a distinct dry season, contrary to previous views. The role of C. americanus as a staple is difficult to assess; it might have been used for special purposes, e.g. beer brewing. In spite of extensive screening, we did not detect any banana phytoliths in the EIA samples. Musa phytoliths were only present in LIA contexts after ca. ad 1400, leaving room for the possibility that the introduction and spread of Musa spp. AAB ‘Plantain’ in the ICB was a late phenomenon.

Advancing Ocean Governance in Marine Regions Through Stakeholder Dialogue Processes - Laura Weiand; Sebastian Unger; Julien Rochette; Alexander Müller; Barbara Neumann (Frontiers in Marine Science, 2021)
The poor state of the ocean and the transboundary nature of the marine environment require bold action by States coordinated across sectors and territorial boundaries in order to deal with the manifold challenges the ocean is facing—and with it humankind. Cooperation and coordination among States and stakeholders in marine regions have proven to be important levers for policy implementation and to strengthen ocean governance, yet remain challenging. Transparent and engaging stakeholder dialogue processes have the potential to provide guidance for the necessary transformation toward ocean sustainability and support the attainment of Sustainable Development Goal (SDG) for the ocean, SDG 14 and other interlinked ocean-related targets. The aim of this study is to review the challenges and opportunities of current collaborative efforts, namely multi-stakeholder dialogue and exchange processes, within and between marine regions to accelerate transformative action, contributing to these global goals. This paper builds on knowledge co-production and collaborative governance literature, and reviews experiences by stakeholders with ocean-related science-policy interfaces in an effort to strengthen regional ocean governance. As an exemplary case of such interfaces, this study assesses the Marine Regions Forum, a newly established inclusive dialogue and exchange platform for diverse actors from marine regions that aims to provide an informal space for joint learning and support regional action and international governance processes alike. Employing latent content analysis of interviews with experts, critical common barriers that hamper current collaborative efforts amongst stakeholders in marine regions are identified, such as fragmented governance frameworks, power and resource imbalances, and lack of meaningful stakeholder engagement. Pathways to address these challenges, such as through common goal orientation, contextualisation, inclusivity, trust building and meaningful continuous interactions are also identified. This paper concludes by discussing the value added of transparent and inclusive collaborative processes in the transformation of ocean governance toward achieving sustainability.

Mapping interactions between the sustainable development goals: lessons learned and ways forward - Måns Nilsson; Elinor Chisholm; David Griggs; Philippa Howden-Chapman; David McCollum; Peter Messerli; Barbara Neumann; Anne-Sophie Stevance; Martin Visbeck; Mark Stafford-Smith (Sustainability Science, 2018)

Strong sustainability in coastal areas: a conceptual interpretation of SDG 14 - Barbara Neumann; Konrad Ott; Richard Kenchington (Sustainability Science, 2017)

Extraradical development and contribution to plant performance of an arbuscular mycorrhizal symbiosis exposed to complete or partial rootzone drying - Elke Neumann; Barbara Schmid; Volker Römheld; Eckhard George (Mycorrhiza, 2009)

Spatial modelling for the development of agri-environmental programs - Barbara Neumann; Michael Lütz; Beatrice Schüpbach; Erich Szerencsits (Regional Environmental Change, 2009)

A multimodal brain-based feedback and communication system - Thilo Hinterberger; Nicola Neumann; Mirko Pham; Andrea Kbler; Anke Grether; Nadine Hofmayer; Barbara Wilhelm; Herta Flor; Niels Birbaumer (Experimental Brain Research, 2004)

Four thousand years of plant exploitation in the Chad Basin of northeast Nigeria I: The archaeobotany of Kursakata - Marlies Klee; Barbara Zach; Katharina Neumann (Vegetation History and Archaeobotany, 2000)

Detection of developmentally regulated genes of the myxobacterium Stigmatella aurantiaca with the transposon Tn5lacZ - Andreas Pospiech; Bjrn Neumann; Barbara Silakowki; Hans Ulrich Schairer (Archives of Microbiology, 1993)